Facile synthesis of MOF-derived Mn2O3 hollow microspheres as anode materials for lithium-ion batteries. Issue 96 (30th September 2016) - Zheng, Fangcai; Xu, Shihao; Yin, Zhichen; Zhang, Yuanguang; Lu, Lu
Abstract : In this article, we report a facile and scalable route for the fabrication of Mn2 O3 hollow microspheres by direct pyrolysis of Mn-based metal–organic frameworks at 450 °C with a heating rate of 10 °C min −1 in air. Abstract : In this article, we report a facile and scalable route for the fabrication of Mn2 O3 hollow microspheres by direct pyrolysis of Mn-based metal–organic frameworks at 450 °C with a heating rate of 10 °C min −1 in air. The effect of the heating rate on the morphology of the final samples has been also investigated. When evaluated as an anode material for LIBs, these Mn2 O3 microspheres exhibited a reversible and stable capacity of 582 mA h g −1 after 60 cycles at a current density of 100 mA g −1 . The improved capacity and excellent cycling stability of the as-prepared Mn2 O3 microspheres could be attributed to the porous hollow structures, which can reduce diffusion length for lithium ions and electrons, and also can enhance structural integrity for buffering the volume expansion during the discharge/charge processes.